Effect of a Pharmacist-Led Program on Improving Outcomes in Patients with Type 2 Diabetes Mellitus from Northern Cyprus: A Randomized Controlled Trial - SANCAR, MESUT (ACAD MANAGED CARE PHARMACY, 2017)
BACKGROUND: The management of type 2 diabetes mellitus is complex, requiring continuous medical care by health care professionals and considerable self-care efforts by patients. Pharmacist-led care programs have been shown to help patients with diabetes succeed in achieving treatment goals and improving outcomes. Pharmacist-led care is a new health care concept in Northern Cyprus. OBJECTIVE: To evaluate the effect of a pharmacist-led care program on glycemic control, determined by hemoglobin A1c (A1c), and secondarily on blood pressure, lipid profile, body mass index (BMI), waist circumference, medication adherence, and self-care activities, for patients with type 2 diabetes over a 12-month period. METHODS: This was a prospective, randomized controlled study conducted in a public hospital's outpatient diabetes clinic, with 152 patients who had been diagnosed with type 2 diabetes. Of these, 75 patients were in the intervention group, and 77 patients were in the usual care group. The intervention group participated in a pharmacist-led care program with a clinical pharmacist who provided 5 face-to-face educational sessions over a period of 12 months. The main outcome measure was change in A1c, and secondary outcome measures were changes in fasting blood glucose, systolic and diastolic blood pressure, lipid values (total cholesterol, low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C], and serum levels of triglycerides [TGs]), BMI, waist circumference, self-reported medication adherence (Morisky-Green test), and self-care activities. Changes in outcome measures from baseline to the end of the study were assessed using the Mann-Whitney U-test and Wilcoxon test. RESULTS: At the end of the 12-month study period, the intervention patients showed a greater reduction in A1c values than the usual care patients (-0.74% vs. -0.04%; P < 0.001). Both groups showed significant reductions in fasting blood glucose levels between baseline and the end of 12 months; the difference between the groups was statistically nonsignificant (P=0.410). When comparing the intervention and usual care groups, there was a significant decrease in systolic (P=0.01) and diastolic blood pressure (P=0.04) at the end of the trial. No significant differences were found between the groups in LDL-C, HDL-C, or TG values; however, total cholesterol levels did decrease significantly (P= 0.063, 0.331, 0.896, and 0.04, respectively). Significant reductions occurred in BMI (P < 0.001) and waist circumference (P < 0.001), and improvements were observed in self-reported medication adherence and self-care activities in the intervention group. CONCLUSIONS: A clinical pharmacist-led care program in a public hospital's outpatient diabetes clinic was associated with significant improvements in reducing A1c and other secondary outcomes in a 12-month randomized controlled study.
Keywords: PHARMACEUTICAL CARE PROGRAM; BODY-MASS INDEX; MEDICATION ADHERENCE; SELF-MANAGEMENT; INTERVENTIONS; MORTALITY; ADULTS; METAANALYSIS; ASSOCIATION